A stochastic short‐term operation model for an active distribution company considering network constraints and demand response. (2nd February 2017) - Cai, Yu; Lin, Jin; Wan, Can; Song, Yonghua
Summary: This article proposes a short‐term operation model for an active distribution company (ADisCo) acting as a producer to maximize its profit from selling energy in electricity markets. The model is constructed based on a 3‐stage stochastic programming framework to represent the trading in the day‐ahead market, the adjustment market, and the real‐time operation as well as uncertainties about market prices and distributed generations (DGs). A novel optimal operation model of distribution network is developed and integrated into the stochastic programming framework to well address the network securities of congestions and voltage violations because of the integration of DGs and interruptible loads. Accordingly, the proposed stochastic operation model is formulated as a linear programming model that can be efficiently solved by commercial software without resulting in further numerical troubles, indicating highly practical potential for industrial utilizations. A variety of case studies demonstrate the effectiveness of the proposed model for an ADisCo on security enhancements and operation revenue increases.